Preparation, characterization, biological activity, density functional theory calculations and molecular docking of chelates of diazo ligand derived from m‐phenylenediamine and p‐chlorophenol. (4th April 2017) - Mahmoud, Walaa H.; Mohamed, Gehad G.; Refat, Ahmed M.
Abstract : A novel azo dye ligand, 2, 2′‐(1, 3‐phenylenebis(diazene‐2, 1‐diyl))bis(4‐chlorophenol), was synthesized from the diazotization of m ‐phenelyenediamine and coupling with p ‐chlorophenol in alkaline medium. Mononuclear Cr(III), Mn(II), Fe(III), Co(II), Ni(II), Cu(II), Zn(II) and Cd(II) complexes of the azo ligand (H2 L) were prepared and characterized using elemental analyses, infrared spectroscopy, electron spin resonance, magnetic susceptibility, conductance measurements and thermal analyses. The UV–visible, 1 H NMR and mass spectra of the ligand and its chelates were also recorded. The analytical data showed that the metal‐to‐ligand ratio in the mononuclear azo complexes was 1:1. Diffuse reflectance and magnetic moment measurements revealed the complexes to have octahedral geometry. The infrared spectral data showed that the chelation behaviour of the ligand towards transition metal ions was through phenolic oxygen and azo nitrogen atoms. The electronic spectral results indicated the existence of π → π* (phenyl rings) and n → π* (─N═N) and confirmed the mentioned structure. Molar conductivity revealed the non‐electrolytic nature of all chelates. The presence of water molecules in all complexes was supported by thermal studies. Molecular docking was used to predict the binding between H2 L and the receptors of breast cancer mutant 3hb5‐oxidoreductase, crystal structure of Escherichia coli (3 t88) and crystal structure of Staphylococcus aureus (3q8u). The molecular and electronic structure of H2 L was optimized theoretically and the quantum chemical parameters were calculated. In addition, the effects of the H2 L azo ligand and its complexes on the inhibition of bacterial or fungal growth were evaluated. The prepared complexes had enhanced activity against bacterial or fungal growth compared to the H2 L azo ligand. Abstract : Mononuclear complexes of the prepared azo ligand with different transition metal ions were synthesized. The nature of bonding of the complexes deduced from elemental analyses, spectral studies, conductivity measurements, thermogravimetric analyses and further confirmed by X‐ray powder diffraction, also the quantum chemical parameters were calculated. The antimicrobial data reveals that azo ligand show inhibition capacity less than the corresponding complexes against all the species under study, in addition to molecular docking with different proteins was performed.